The impact of cultural capital on school performance - Nunes, Alexandre Chaves; Andrade, Josemberg Moura de (Frontiers in Education, 2024)
Introduction: We define cultural capital as a set of assets or resources accumulated over a lifetime through relationships and events in the family environment. We analyze cultural capital under two dimensions: static cultural capital (SCC) and relational cultural capital (RCC). The objective of this study was to verify the effect that cultural capital has on students' academic performance. Method: The research included the participation of 11,795 students who were classified into four levels of cultural capital, in each of the two dimensions: G1 – Critical, G2 – Low, G3 – Medium and G4 – High. Statistical analyses such as ANOVA, Student's t-test and factorial design showed the impact of cultural capital in the combination of the different groups with the subjects of Portuguese and mathematics. Results: The results led us to conclude that: 1) cultural capital, in both dimensions, impacts the students' academic performance, both in Portuguese, F(3, 11764) = 9.516, with p < 0.001 and η2 = 0.002, F(3, 11764) = 42.349, with p < 0.001 and η2 = 0.011, and in mathematics, F(3, 11764) = 13728, with p < 0.001 and η2 = 0.003, and F(3, 11764) = 28.138, with p < 0.001 and η2 = 0.007, and; 2. RCC linearly impacts student performance as SCC is increased, F(9, 11771) = 1.869, with p = 0.052 and η2 = 0.001. Conclusion: 1. cultural capital impacts students' academic performance, but most notably in the Portuguese language discipline; 2. The dimensions of cultural capital behave differently and the excess of SCC, without the presence of RCC, impacts the reduction of medium performance. 3. The RCC linearly impacts student performance as the SCC is increased.